Are you in(gaged)? The importance of engagement and experience on employees and organizations' success - da Costa, L. R.; Loureiro, S. M. C. (2018 Global Marketing Conference, 2018)
This study intends to analyse the impact of the engagement and employee experience towards the employee and employer success. The results demonstrate that organisations are conscious of the importance of retain and create happiness at work and are starting to create an internal experience for their workforce. They want to have employees engaged and retain talent. When employees are more committed to be happier at work they tend to take part of the ownership of their organisations. Employers and employees are more focused on people and the value that they can add to every single product and/or service they design, create and deliver. All this investment on internal world is feeding a better consumer experience as the quality standards are getting higher.